# Graficas

Páginas: 2 (360 palabras) Publicado: 15 de noviembre de 2011
FUNCIONES TRIGONOMETRICAS

y=sin(x^2)

y=sin(x)

y=sin(x+2)^(1/2)

y=sin(x+2)*(x)

y=sin (2/x) (x)

y=cos(x)y=cos(x)^(1/3)

y=cos(x-1)

y=cos(x-1)+(3x)

y=cos(-x/4)

y=tan(x)

y=tan(x^2)-1

y=tan ((x)^(1/2))/2

y=tan(2x-5+x)

y= tan(x/2)y=cot(x)

y=cot(x-2x)

y=cot(x-2x)^2

y=cot(2/x)

y=cot(x-2)+(x)^(1/3)

y=sec (x)

y=sec (x)(2x)

y=sec (-2x)^3

y=sec(2x/2x)

y=sec (3x)^(1/2)

y=csc (x)

y=csc (x)^2

y=csc (x+1^x)

y=csc (-1)(x^2)

y=csc(3)-(1/x)

POLINOMIALES Y RACIONALESy=x^2+x+1

y=x^2+3x+1

y=2(x^2)+3x+1

y=x^2+5x+0

y=16x^2+5x+2

y=x^3+x^2+5x+2

y=-x^3+x^2+5x-2

y=2x^3+x^2+x+3y=2x^3+2x^2+4x-1

y=x^3-x^2+4x-5

y=(x)^(1/2)

y=(x+2X)^(1/2)

y=(-x)^(1/2)

y=(X^2)^(1/2)

TRIGONOMETRICAS INVERSAy=asin (x)

y=asin (x^2)

y=asin (x-1)

y=asin (2x+1)

y=asin (X)^(1/2)

y=acos (X)

y=acos (X^2)

y=acos (2X+1)*x

y=acos(2/x)

y=acos (x/2)

y=atan (x)

y=atan (x^2)

y=atan (2x-1)

y=atan (2x-1)^(1/2)

y=atan (1/x)(2x)

y=acot (X)

y=acot(X)^(1/2)

y=acot (X+2x)^(1/2)

y=acot (X-1)^(1/2)*2

y=acot (2x)(x^2)-2

y=asec (x)

y=asec (x)^(1/2)

y=asec (x^2+2x-2)y=asec (x)-((2-x)^(1/2))

y=asec (x-3)^3

y=acsc (x)

y=acsc (x-1)

y=acsc (x-1)^(1/2)

y=acsc -x^2+3x-5

y=acsc -x+2(x)

Regístrate para leer el documento completo.